La destinée anglaise de l’Inventaire de Jean de Serres : traduction, réécriture et transformation formelle du livre pour construire la mémoire des guerres de Religion (1597-1624) - Marie-Céline Daniel (XVII-XVIII)
This article examines the English translation of Jean de Serres’s Inventory of the general history of France. The book, first published in France in 1597 and later on continued by various authors, was translated in London by Edward Grimeston and published in several editions from 1607 onwards. Compared to modern-day appraisals of translation works, Grimeston’s opus is a different book altogether – he adds, suppresses, or corrects passages that do not fit in the English understanding of the French Wars of Religion. In addition, a change in format – from in-12 to folio – contributed to changing the nature of the book, from an easy-to-carry small volume to a larger, more official-looking volume of educated reading. Doing so, along with his publisher George Eld, Grimeston may be considered as a full author of a new book perpetuating the memory of the French religious strife.